Let there be (a new kind of) light [NEWS]. - Boyd, J. (IEEE spectrum)
Recent events on the business front and advances in the lab could soon transform the way about lighting our homes and buildings. Significant strides in developing organic light-emitting diodes (OLEDs) may allow architects in the next few years to integrate this power-efficient and tractable technology into basic building materials, enabling entire structures to be turned into luminous edifices. Konica Minolta Holdings, a Tokyo-based manufacturer of imaging products, and General Electric Co., one of the world's largest lightbulb makers, formed a strategic alliance to accelerate development of OLED lighting and vowed to ship products in the next three years. A major challenge all OLED manufacturers face is how to make their products cost-competitive with the ultracheap incandescent and fluorescent lighting products on the market.